Designing Steel Warehouse Layouts: A Comparative Study of Dedicated Storage and Class-Based Storage Methods at PT. BSB - Maghrobi Muzzaky Pratama; Said Salim Dahda (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
PT BSB is a company engaged in steel fabrication manufacturing. There are various kinds of projects carried out at the company, namely bridges, steel structures, buildings, towers, etc. and the irregular placement of steel in the warehouse results in problems in the steel storage warehouse at PT. BSB where the company does not have an arrangement regarding the layout of raw materials for steel retrieval has difficulty because the steel is stored randomly without paying attention to its type and is only placed in an empty place. Therefore, it is necessary to design a layout using the dedicated storage and class-based storage methods to improve the warehouse layout by designing a warehouse layout so that it can make it easier to find and minimize steel search time. Results of research carried out obtained that distance travelled using the dedicated storage method is amounting to 7790,85 metres with material handling time 15581,7 minutes, whereas with use class based storage method can be obtained distance 8382,05 metres with material handling time 16764,1 minutes. Concluded that design results Select the selected layout is with use possible dedicated storage method reduce distance travel and time at PT. BSB warehouse becomes more practice and efficient